Nutritional and Functional Assessment of Hospitalized Elderly: Impact of Hospitalized Elderlyin Babil, Iraq - Ali, Noor Sabri; Mohammed, Salam Jasim (Medical Science Journal for Advance Research, 2025)
Background: Malnutrition is a common condition in older people. Growing evidence showed a high prevalence of malnutrition and functional decline among hospitalized elderly patients. This is primarily due to challenges in identifying and appropriately managing at-risk patients. Aim: To assess the nutritional and functional status of hospitalized elderly and to study their associations with sociodemographic variables. Methodology: A cross-sectional study was carried out on 300 elderly patients admitted to Murjan Teaching Hospital in Babil governorate\ AL-Hilla City, Iraq. The data was collected from the beginning of March to the end of August 2024. A well-structured questionnaire was used to gather information about the participants' sociodemographic features. Comprehensive geriatric assessments, including nutritional and functional evaluations, were done according to the nutritional checklist and Barthel index. Data were analyzed using the SPSS program version 26. Results: The mean age of the study elderly was 71.38±8. 807 years. The largest age category was 60-69 years (43.7%), and 58% were females. According to the nutritional checklist, 77.7% of participants were at high risk, 18.7% were at moderate risk of malnutrition, and 3.7% had good nutritional status. The Barthel index score showed that 44.3% of the elderly had poor functional activity,25.3% had limited functional activity, and 30.3% had good functional activity. There was a significant association of functional decline with age, education, occupation, marital state, income, and absence of close friends (p<0.05). A significant association was noticed between sexual activity and both nutritional and functional status (p<0.05). Conclusions: A high proportion of hospitalized elderly patients are at risk of malnutrition and functional decline. Older age groups, widows, illiterate individuals, and low-income individuals without close friends were risk factors for poor functional ability.